Implementation of the Syirkah Agreement in Halal Business Crowdfunding Schemes: Opportunities and Regulatory Challenges in Indonesia - Asikin, Ridwan Ibnu; Amaliah, Ima; Nurhayati, Nunung (Journal of Social Science and Business Studies, 2026)
The rapid development of Indonesia’s digital economy has fostered financial innovations such as crowdfunding, which enables collective fund mobilization to support business activities. Within this context, halal business crowdfunding has emerged as a promising financing alternative for Micro, Small, and Medium Enterprises (UMKMs), aligning with the country’s efforts to strengthen its Islamic economic ecosystem. However, the implementation of syirkah contracts which emphasize principles of partnership, justice, transparency, and proportional profit and loss sharing within Indonesia’s crowdfunding framework still faces significant challenges. Although DSN–MUI Fatwa No. 114/2017 on Syirkah and Fatwa No. 140/2021 on Sharia-Based Securities Crowdfunding provide a normative foundation, the absence of explicit regulation in OJK Regulation No. 57/POJK.04/2020 has created legal ambiguity and inconsistent practices among platforms such as ALAMI, Ethis, and SHAFIQ.id. This study adopts a qualitative descriptive approach using literature analysis and critical synthesis of expert findings to examine the implementation, challenges, and opportunities of syirkah contracts in halal business crowdfunding schemes in Indonesia. The findings reveal that structural gaps exist between positive law (OJK regulations) and Sharia economic law, resulting in limited regulatory support, weak Sharia Supervisory Board (DPS) oversight, and insufficient technical standards for profit sharing and transparency. Furthermore, asymmetric information, such as limited investor access to real project financial data and flat profit-sharing practices, undermines compliance with syirkah principles.